Screening, Diagnosis, and Prevention in Clinical Practice: Evidence from Argentine and Latin American Medicine (English Version) (South American Publishing, 2026)
Local tax systems play a central role in the relationship between governments and citizens, especially in decentralized settings where municipalities finance essential public services. Evidence from Colombia shows that tax performance depends on the interaction between regulatory frameworks, institutional practices, digital tools, and social perceptions. Factors such as tax culture, citizen trust, legal enforcement, and administrative strategies shape compliance beyond coercion alone. By combining empirical analysis with governance perspectives, this approach highlights how transparency, institutional credibility, and public intelligence are key to strengthening local taxation, fostering compliance, and supporting inclusive and sustainable development.